ANALISIS CONSUMER ETHNOCENTRISM DAN PERCEIVED VALUE TERHADAP MINAT BELI KONSUMEN DENGAN BRAND IMAGE SEBAGAI MEDIATOR - Permatasari, Meirina Indah; Soesanto, Harry (Diponegoro Journal of Management, 2015)
This study aimed to analyze the influence of consumer ethnocentrism and perceived value to purchase intention using brand image as mediator study case on consumer of Batik Semarang. This study used two independent variables are consumer ethnocentrism and perceived value, purchase intention variable as a dependent variable and then brand image variable as an intervening variable.            Simple random sampling method is used for this research. Sample were collected from 100 respondents who ever had experienced to buy Batik Semarang. Multiple regression analysis is used for this study.            The results showed that consumer ethnocentrism have positive effect to brand image, perceived value have positive and significant effect to brand image and consumer ethnocentrism, perceived value, brand image have positive and significant effect to purchase intention.